2011
DOI: 10.1080/10889868.2011.570281
|View full text |Cite
|
Sign up to set email alerts
|

Colonization and Degradation of Thermally Oxidized High-Density Polyethylene byAspergillus niger(ITCC No. 6052) Isolated from Plastic Waste Dumpsite

Abstract: Plastic materials, particularly polyethylene, are the potential source of environmental pollution. In the present study, a fungal strain was isolated from plastic waste dumpsites capable of adhering to high-density polyethylene (HDPE) surface. The fungal strain was identified as Aspergillus niger (ITCC no. 6052). A visible increase in the growth of the fungi was observed on the surface of the polyethylene when cultured in minimal medium at 30 • C and 120 rpm, for 1 month. Approximately 3.44% reduction (gravime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 21 publications
(21 reference statements)
0
13
0
1
Order By: Relevance
“…Studies on fungal mediated degradation of polyethylene has previously been reported using Mucor rouxii and Aspergillus flavus (El-Shafei et al, 1998), Phanerochaete chrysosporium (Liyoshi et al, 1998), Penicillium simplicissimum YK (Yamada-Onodera et al, 2001) and Aspergillus niger ITCC no. 6052 (Mathur et al, 2011). This study aims to isolate and identify the polyethylene degrading efficient fungal strains without any pre-treatment, pro-oxidant additives and also attempts to understand the degradation ability of two fungal strains, Aspergillus tubingensis VRKPT1 and A. flavus VRKPT2.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on fungal mediated degradation of polyethylene has previously been reported using Mucor rouxii and Aspergillus flavus (El-Shafei et al, 1998), Phanerochaete chrysosporium (Liyoshi et al, 1998), Penicillium simplicissimum YK (Yamada-Onodera et al, 2001) and Aspergillus niger ITCC no. 6052 (Mathur et al, 2011). This study aims to isolate and identify the polyethylene degrading efficient fungal strains without any pre-treatment, pro-oxidant additives and also attempts to understand the degradation ability of two fungal strains, Aspergillus tubingensis VRKPT1 and A. flavus VRKPT2.…”
Section: Introductionmentioning
confidence: 99%
“…3a, b. Mathur et al (2011) the microbial adhesion to the surface of polymer is a preliminary step for biodegradation to take place (Moriyama et al 1993). Microorganisms colonize the polymer surface and adhere by extracellular polymer production.…”
Section: Surface Morphology Study Of Ldpementioning
confidence: 99%
“…After colonizing onto the plastic surface. They allow entrapment of fungi and succession of other species (Mathur et al, 2011). It allows sharing of metabolic intermediates and accelerates degradation (Gilan et al, 2004).…”
Section: Fungusmentioning
confidence: 99%